Pickering Emulsions: An Emerging Clean-label Emulsion Technology and its Applications in the Food Industry - Divyashree M; Ganga A; Samit Dutta (Archives of Current Research International, 2025)
Pickering emulsions, stabilized by solid particles instead of traditional surfactants, have garnered significant attention for their potential applications in the food industry. This review explores the fundamental principles, and provides a comprehensive overview of the mechanisms behind the stabilization of Pickering emulsions, with theories on the adsorption of solid particles at the oil-water interface mechanisms, significant parameters affecting the stability of emulsion such as wettability, particle size, shape, surface charge, etc. Additionally, various preparation methodologies for creating Pickering emulsions, including high-energy and low-energy methods are mentioned. Their key applications in beverages, dairy products, sauces, dressings, packaging, and preservation are highlighted along with a brief description of how they enhance texture, stability, and product performance is reported. Their advantages, particularly the role in creating stable, natural, and clean-label food products and challenges for their commercial applications been discussed. Being a novel approach in emulsion technology. Pickering emulsions are the active area for research for developing sustainable emulsions for the food industry.